IMPLEMENTASI E-LEARNING DUOLINGO SEBAGAI UPAYA PENGEMBANGAN MODEL PEMBELAJARAN BAHASA MANDARIN DI SMKI TAMAN SISWA PURWOKERTO - Chendy Arieshanty Paramytha; Eko Kurniawan; Zuyinatul Isro; Dyah Tjaturrini (Jurnal Abdimas Bina Bangsa, 2023)
Community Service with the title "Implementation of Duolingo E-learning as an Effort to Develop a Mandarin Language Learning Model at Taman Siswa Purwokerto Vocational School" aims to: l) provide science and technology-based training by utilizing Duolingo e-learning in Mandarin, the learning process is in accordance with teaching materials and student abilities , 2) implementing Duolingo e-learning in the learning process with student center learning, 3) advanced learning based on Duolingo e-learning to develop a Chinese language learning model at Taman Siswa School Vocational School. As one of the efforts developed by the school is to provide opportunities for teachers and students to participate actively in developing an effective and efficient learning process. The problem faced by SMK Taman Siswa is the limited teaching media owned by Mandarin teachers. Therefore, there is a need for science and technology-based training by utilizing e-learning for teachers and students at SMK Taman Siswa Purwokerto. The method used in this training activity is to provide intensive training on the use of Duolingo e-learning in the process of learning Mandarin. Measurement is done by way of question and answer using guidelines which are carried out at the beginning as a situation analysis and at the end as an evaluation. The outputs generated from this activity were in the form of articles presented at the National Seminar and the results of a basic monograph on tourism in Mandarin as a professional tour guide.